Character-Based Curriculum and Textbook Development in Indonesia: A Critical Review - Jazadi, Iwan (SOSIOHUMANIKA, 2015)
ABSTRACT: Education in Indonesia is declared to be in an emergency state, whereas a lot of innovative policies have been offered, mainly since the availability of education reform and autonomy in 2003. This situation illustrates the world of education in Indonesia are still many weaknesses and needs to be revised thoroughly. The education process, however, should be fun, child-centered, and that new curriculum policies have to be rooted in the people and exempted from short-term political interests. The writer argues that the national education system can be improved through developing character-based curriculum and textbooks by fulfilling four criteria, those are: the adoption of a broader conception of curriculum; participatory curriculum decision making; a critical analysis of characteristic values in textbooks; and developing character education by integrating good values into the textbooks and in other activities either planned or in those forming the hidden curriculum. Empirical findings from primary research and observation on the implementation of the 1994 Curriculum, Competency-Based and School-Based Curriculum (2006), and 2013 Curriculum, which are analyzed in lights of curriculum and textbook theories and practices from around the world, form the argumentative strengths of this article. The character education program has to be integrated in the curriculum revision and preparation of textbooks.KEY WORD: Indonesian education, formal curriculum, hidden curriculum, textbooks, character values, integrating good values, and character education.Â RESUME: âPengembangan Kurikulum dan Buku Teks Berbasis Karakter di Indonesia: Sebuah Tinjauan Kritisâ. Pendidikan di Indonesia disinyalir mengalami keadaan gawat-darurat, padahal berbagai kebijakan inovatif telah dilaksanakan, terutama sejak bergulirnya reformasi dan otonomi pendidikan sejak tahun 2003. Keadaan ini menggambarkan dunia pendidikan di Indonesia masih banyak kelemahan dan perlu dibenahi secara menyeluruh. Proses pendidikan, walau bagaimanapun, hendaknya menyenangkan, berpusat pada peserta didik, dan kebijakan kurikulum baru harus berakar di masyarakat serta dibebaskan dari kepentingan politik sesaat. Penulis berargumen bahwa sistem pendidikan nasional akan dapat dibenahi melalui pengembangan kurikulum dan buku teks berbasis karakter, dimana penataan tersebut harus memenuhi empat persyaratan fundamental, yaitu: pengadopsian konsepsi kurikulum secara luas; pembuatan keputusan kurikulum secara partisipatif; penelaahan kritis nilai-nilai karakter didalam buku teks; dan pengembangan pendidikan karakter dengan pengintegrasian nilai-nilai karakter kedalam buku teks dan kegiatan-kegiatan lainnya, baik yang terencana maupun yang merupakan bagian dari kurikulum tersembunyi. Temuan empirik dari penelitian primer dan pengamatan tentang penerapan Kurikulum 1994, KBK-KTSP atau Kurikulum Berbasis Kompetensi â Kurikulum Tingkat Satuan Pendidikan (2006), dan Kurikulum 2013, yang ditelaah secara kritis berdasarkan teori dan praktek kurikulum dan buku teks dari berbagai belahan dunia, membentuk kekuatan argumentasi tulisan ini. Program pendidikan karakter harus diintegrasikan dalam revisi kurikulum dan persiapan buku teks.KATA KUNCI: Pendidikan Indonesia, kurikulum formal, kurikulum tersembunyi, buku teks, nilai karakter, integrasi nilai-nilai baik, dan pendidikan karakter.About the Author: Iwan Jazadi, Ph.D. is a Lecturer and Chairman of STKIP (College of Education and Teacher Training) Paracendekia NW Sumbawa, Jalan Lintas Sumbawa Bima Km.5, Sumbawa Besar, Nusa Tenggara Barat, Indonesia. For academic interests, the author is able to be contacted via mobile phone at: +62810915923077 or via e-mail at: iwanjazadi@gmail.comHow to cite this article? Jazadi, Iwan. (2015). âCharacter-Based Curriculum and Textbook Development in Indonesia: A Critical Reviewâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.8(2) November, pp.313-330. Bandung, Indonesia: Minda Masagi Press and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (October 5, 2015); Revised (November 10, 2015); and Published (November 30, 2015).